EFFICACY OF HIGH AND LOW DOSE ORAL VITAMIN D REPLACEMENT THERAPY IN INFLAMMATORY BOWEL DISEASE (IBD): SINGLE CENTRE COHORT. (8th June 2013) - Hiew, H J; Naghibi, M; Wu, J; Saunders, J; Cummings, F; Smith, T R
Abstract : Introduction: IBD patients are at risk of micronutrient deficiency including vitamin D. There is evidence that vitamin D deficiency is associated with poor disease activity. Aims/Background: To determine the vitamin D status and evaluate the effectiveness of oral vitamin D treatment in a sub-set of IBD patients at a University Hospital. Method: All IBD patients with serum vitamin D levels measured in 2011 were identified. Vitamin D deficiency was determined as plasma 25-hydroxyvitamin D levels <52 nmol/L. Oral vitamin D treatment was classified as 'low dose' when patients prescribed daily 800 units of vitamin D2/D3 and 'high dose' when given either 100'000 units once or 50'000 units weekly for 6 weeks. Treatment response was assessed within 6 months of treatment. Results: 205 IBD patients had their plasma vitamin D measured. 95 (46%) were found to be vitamin D deficient with no significant difference in the prevalence between Crohn's disease (CD) and ulcerative colitis (UC) patients (p=0.449). 32 treatment episodes had follow up measurement. Those who received 'high dose' regimen demonstrated a 150% increase in plasma vitamin D compared to a 34% increase in those put on 'low dose' regimen (p=0.001). There was no significant difference in treatment response between CD and UC patients (p=0.874) (table 1 ). Conclusion: Oral vitamin D replacement is an effective treatment for vitamin D deficiency in IBD patients and appears to be dose responsive, in both UC and CD patients. The optimal dose of oral vitamin D supplementation is yet to be determined, but higher doses are significantly more effective.